Christianity in the Kyrgyz Republic: the activities of the Russian Orthodox Church and baptism policy of Western missionary organizations (Journal of Philosophy Culture and Political Science, 2018)
This article explores the role of Christianity in the Kyrgyz Republic. Describes the activities of the RussianOrthodox Church and the activities of Western Protestant missionary organizations.Initially, given a breef history of missionary activity and the spread of Christianity in Central Asia and in theterritory of Kyrgyzstan. Also disclosed is the history and characteristics of stages in the spread of the RussianOrthodox Church, describes the current state of relations between the Russian Orthodox Church and the state, itsplace and role in society.Describes the activities of the new Protestant organizations baptism population, posing a threat to the unityand integrity of the state and society. According to the above areas we study defi nition and the role of Christianityin Kyrgyz society.Key words: Christianity, Russian Orthodox Church, the Western Protestant organizations, missionarywork , democracy.